Multiple sclerosis and COVID-19: a bidirectional Mendelian randomization study - Liu, Shitong; Liang, Yixin; Sheng, Binbin; Zhang, Rongxin (Frontiers in Immunology, 2024)
This study aims to investigate the potential relationship between multiple sclerosis (MS) and COVID-19 outcomes using Mendelian randomization analysis. Specifically, it evaluates whether genetic factors, including the SNP rs10191329, influence the susceptibility of MS patients to three COVID-19 outcomes (SARS-CoV-2 infection, hospitalized COVID-19, and severe COVID-19). This study utilized genome-wide association study summary statistics from the International Multiple Sclerosis Genetics Consortium to conduct a Mendelian randomization analysis. SNPs strongly associated with MS were selected to examine their impact on COVID-19 outcomes. The analysis focused on identifying any causal associations between MS and COVID-19 severity, as well as assessing the role of interferon beta (IFNβ) treatment in modifying these outcomes. The results suggest a potential association between MS and an increased risk of COVID-19, but individuals carrying the rs10191329 SNP appeared less likely to develop severe COVID-19. This SNP, located within the DYSF-ZNF638 locus, may influence immune responses and MS severity, highlighting its relevance for personalized treatment strategies. Importantly, no significant causal relationship was found between IFNβ treatment and the three COVID-19 outcomes, indicating that the findings in treated patients differ from those observed in untreated patients. This suggests that IFNβ may offer protective effects against SARS-CoV-2 in MS patients. These findings underscore the importance of genetic factors, such as rs10191329, in shaping the clinical outcomes of MS patients in the context of